Adaptasi dan Transformasi Fungsi Rumoh Aceh dalam Konteks Modern (Studi Kasus Rumoh Bapak Awi di Desa Pu’uk Kecamatan Kembang Tanjung) - Magfirah, S; Mirsa, R (Jurnal MESIL (Mesin Elektro Sipil), 2025)
Rumoh Aceh is a traditional Acehnese house that has deep functions and meanings as a reflection of the customary and cultural values of the community. However, the times and social changes have brought transformation to the function and meaning of Rumoh Aceh, especially in the area of Kembang Tanjung. This research aims to analyze the transformation that occurs in the function and meaning of Rumoh Aceh in the region, both from the physical and symbolic aspects. This research uses a descriptive qualitative approach with data collection methods in the form of observation, interviews and documentation. The theory used in this research is the theory proposed by Habraken (1982) regarding transformation and Finke (1990) describing function. The results showed that the function underwent adaptation at the bottom of Rumoh Aceh, which used to function as a cattle drum or warehouse until now modified into additional spaces such as bedrooms, living rooms, TV rooms, dining rooms and kitchens. This transformation reflects the adaptation of the Kembang Tanjung community in maintaining traditional cultural elements amidst the dynamics of modernization. This change is not only influenced by modern needs, but also by people's increasingly diverse understanding of local culture.